Peak Serum Creatinine as a Biomarker of Pancreatic Necrosis in Acute Pancreatitis: A Cross-Sectional Study: Serum Creatinine as a Biomarker of Pancreatic Necrosis in Acute Pancreatitis - Khan, Huma Sabir; Ayyaz, Mahmood; Hanif, Muhammad (Pakistan Journal of Health Sciences, 2024)
Pancreatitis is the inflammation of the pancreas. Pancreatitis can result in pancreatic necrosis which may lead to significant morbidity and mortality. It is possible to predict pancreatic necrosis and organ dysfunction using many biochemical indicators and markers. Peak serum creatinine has been identified as one of such useful markers to predict pancreatic necrosis. Objective: To find the diagnostic accuracy of elevated peak serum creatinine as a predictor of pancreatic necrosis in patients with acute pancreatitis taking the contrast-enhanced computed tomogram scan (CECT) as the gold standard and to establish the degree of agreement between the two clinical tests. Methods: A cross-sectional, analytical study that was carried out at the Department of Surgery, Benazir Bhutto Hospital, Rawalpindi from January 2020 to January 2023. 150 patients diagnosed as having pancreatitis were enrolled in the study. Peak serum creatinine at 48 hours > 1.8 mg/dl was labeled as a predictor of pancreatic necrosis. Contrast-enhanced computed tomogram scan was done within 96 hours of admission. The pancreatic necrosis suggested by raised serum creatinine was confirmed by CECT. The diagnostic accuracy of peak serum creatinine and the degree of agreement between the two modalities was calculated. The Kappa coefficient was used to calculate the strength of agreement. Results: The results show that Peak serum creatinine has a sensitivity of 45.5%, specificity of 97.35%, PPV of 85.0 %, NPV of 93.8 %, and accuracy of 84.6%. This study found that the degree of agreement between raised peak serum creatinine levels and CECT to predict pancreatic necrosis was 84.7% with a “Kappa coefficient” of 0.51. Consequently, the null hypothesis was rejected in light of these findings. Conclusions: It was concluded that elevated serum creatinine (SCr >1.8 mg/dl) at 48 h of admission can be used as a predictor of pancreatic necrosis in patients with acute pancreatitis.